A motivação como ferramenta de melhora escolar - Amorim, Wlisses Leite (2012)
From the school census data from Brazil's 2007 trial, a study was done to assess the impact of motivation on academic success of students. The motivation comes from both the family and teachers, and this is introduced as the questionnaire for students if they respond or not are encouraged by their teachers and / or parents. Through impact assessment model which we used the linear regression technique, using controls to purge the effects of the profiles of students, and approximating the regression coefficient for the desired effect of motivation, we found evidence supporting the hypothesis that the motivation plays a scathing note to the improvement of students' and their respective use in Brazil Exam.